FAKTOR-FAKTOR YANG MEMENGARUHI KONSERVATISME AKUNTANSI (Media Riset Akuntansi, 2022)
This research aims to examine and analyze the effect of financial distress, firm size, leverage, and profitability on accounting conservatism. The population in this study are Miscellaneous Industrial Sector Manufacturing Companies listed on the Indonesia Stock Exchange in 2016 - 2018 which amounted to 132 companies and the sample used amounted to 72 companies. The sampling technique used in the study was the purposive sampling method. The analytical method used is multiple linear regression using SPSS 25 software. The results show that the ratio of firm size and leverage influences accounting conservatism. While financial distress and profitability do not affect accounting conservatism.